The Characeae (Charales, Charophyceae) of Sardinia (Italy): habitats, distribution and conservation. Issue 1 (2nd January 2019) - Becker, Ralf
ABSTRACT: The charophyte flora of Italy is insufficiently known. This paper reports the results of a survey of the historical and recent distribution of Characeae in Sardinia, in order to fill current knowledge gaps. Information about the study area and the database is presented. The study focused on brackish water bodies with a special emphasis on lagoons and temporary brackish pools as well as on freshwater habitats. Between 1988 and 2018 more than 500 water bodies have been investigated. Characeae were recorded in 212 sites. In total, the occurrence of 26 Characean species was verified. They belong to four genera: Chara (13 taxa), Nitella (seven), Tolypella (four) and Lamprothamnium (two). The abundance of the species is discussed and information about their habitats and distribution is given. Distribution maps for selected taxa are presented. During this study Lamprothamnium succinctum was recorded for the first time in Europe. Tolypella salina and Chara baltica were verified as new species for Italy. Moreover, Nitella confervacea and Chara connivens, neither of them recently reported, are confirmed for Italy. A new sexual population of Chara canescens was discovered. As a result of the present study the total number of Characean species known for Sardinia has been increased from 15 to 26. Many taxa, especially nine species closely linked to brackish habitats, are currently very rare throughout Italy. Threats and pressures on Characeae and their habitats in Sardinia are discussed and appropriate actions for their conservation are proposed.